Implementation of the Discrete Fourier Transform (DFT) Steganography Method for Embedding Secret Messages in Digital Image Media - Albert Julio Tampubolon; Ronita Olive Angelie; Saut Parlindungan Manurung (Sean Institute, 2026)
Steganography is a technique for hiding secret information within digital media such as images, audio, or video without raising suspicion. In this study, the Discrete Fourier Transform (DFT) method is applied to embed secret messages into digital images. DFT is a transformation that converts an image from the spatial domain into the frequency domain, allowing data to be embedded into specific frequency components that are not easily detected by the human eye. This research aims to implement and evaluate the DFT steganography method in terms of embedding capacity, stego image quality, and the security of the embedded message. The implementation process includes both embedding and extraction stages. Testing is conducted by measuring Peak Signal-to-Noise Ratio (PSNR) and Mean Square Error (MSE) to evaluate the quality of the stego image. The experimental results show that the DFT steganography method is able to successfully embed messages into digital images with an average PSNR value above 40 dB, indicating very good stego image quality that is not visually detectable. The method also demonstrates good resistance against basic steganalysis attacks. The implementation of the DFT-based steganography application was successfully developed with a user-friendly interface using Python.